Pengaruh Keputusan Investasi, Pendanaan dan Dividen Terhadap Nilai Perusahaan - Purwaningsih, Eny; Siddki , Maulana Ajwa (Nusa Putra University, 2021)
This research was conducted to analyze the effect of investment decisions, funding decisions, and dividends on the value of companies in the manufacturing companies in the food and beverage sector, which are listed on the 2016-2020 Efek Stock Exchange in Indonesia. The sample used in this research is 6 samples of mmanufacturing companies in the food and beverage sector issues listed. The sampling criteria are companies listed on the Indonesia Stock Exchange 2016-2020, companies publishing annual financial reports for the 2016-2020 period in a row, companies having complete financial statement data related to the variables in the study, and the company earned a net profit in the 2016-2020 period. This study aims to analyze and prove empirically the effect of investment decisions, funding decisions, and dividends on firm value. The research data collection method uses secondary data. The sampling method uses the purposive sampling technique. The data analysis method uses multiple regression analysis. Based on the results of the test, it is known that simultaneously, it shows that the investment decisions, funding decisions, and dividend decisions have an effect on the value of the companies in the Indonesian food and beverage sector that are listed in 2016. The results of the partial test show that the investment decision has an significantly positive effect on the value of the company, the funding decision has no significant impact on the value of the company and has an significantly positive effect on this decision.